TANGGAPAN TAMU TERHADAP KUALITAS PELAYANAN CHECK – IN OLEH RESEPSIONIS DI HOTEL DYAN GRAHA PEKANBARU - P. Rajip Malik S Malik S; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Responses in the world of tourism are opinions or perspectives of visitors and tourists in understanding a tourist destination. Hotels are included as basic tourism facilities (main tourism superstructures). This can be seen from the number of tourists who come, of course, they need a place to stop or rest. This research was conducted at Hotel Dyan Graha Pekanbaru Jl. Gatot Subroto No.7, Kota Tinggi, Kec. Pekanbaru City, Pekanbaru City, Riau 28112. This study aims to determine the quality of the check-in service by the receptionist at the Hotel Dyan Graha Pekanbaru and to determine the guest's response to the quality of the check-in service by the receptionist at the Hotel Dyan Graha Pekanbaru. This study uses a quantitative descriptive method, to manage the data obtained in the field through observation, questionnaires and documentation.Information collected to determine guest responses to the quality of receptionist service at Hotel Dyan Graha Pekanbaru using a Likert Scale. (Sugiyono 2004: 86), said that the Likert Scale is used to measure attitudes, opinions and perceptions of a person or group, about events or social phenomena. Data collection techniques used are observation, documentation, and questionnaires/questionnaires. Based on the results of research that has been carried out, the quality of check-in service by the receptionist at the Hotel Dyan Graha Pekanbaru is still required for stable service consistency. Keywords: Guest response, Service, Check – in